The Political Ethics of Kiai - Hannan, Abd (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2023)
This study focuses on examining the political existence of the kyai, the role and populist values behind their political activism as a constructive critique of political dynamics in Indonesia, which in recent years has become increasingly pragmatic. There are three research questions discussed in this study, what are the populist values contained in the political activism of the clerics in Indonesia? What is the political reality in Indonesia today? How to understand the value of kyai political activism as a critique of political pragmatism in contemporary Indonesia? This study uses a type of qualitative research, the data used are primary data and secondary data. After analyzing field data based on the perspective of political sociology theory, this study finds that political pragmatism in Indonesia is currently clearly illustrated along with the increasingly liberal political practices in Indonesia, thus triggering the birth of transactional politics, money politics, and corrupt practices. In order to address this issue, it is important to make the populist values of kyai political activism a constructive criticism in order to return Indonesian politics to its nature, in line with the spirit and system of democracy, both in terms of procedure and substance. The populist spirit behind the kyai's political activism is clearly reflected in their political struggle which tends to fight for two values at once, namely the value of universality and the value of defending personal rights, in this context are human rights and human dignity, as inherited by Gusdur's political thought, Kyai Ahmad Dahlan , Kyai Hasyim Asy'ari, Kyai Sahal Mahfudz and a number of other kyai figures.